Differences in the Transcranial Motor Evoked Potentials Between Proximal and Distal Lower Extremity Muscles. Issue 2 (March 2018) - Parikh, Pooja; Cheongsiatmoy, Justin; Shilian, Parastou; Gonzalez, Andres A.
Abstract : Purpose: Transcranial motor evoked potentials (TcMEPs) are the preferred modality to monitor the integrity of motor pathways during surgery. Recently, it has also been used as a method to help with detection of nerve roots injuries. Adequate baseline muscle responses are vital to detect nerve injury. We have observed that TcMEP responses are not homogeneous across multiple myotomes, but this has not been studied systematically. Our objective is to determine whether there are any relative differences in amplitude or morphology of TcMEPs across various lower extremity muscles. Methods: Clinical and neurophysiological monitoring data from patients who had lumbar spine surgery were obtained retrospectively. Transcranial motor evoked potential responses were evaluated for each limb in the quadriceps, tibialis anterior, and intrinsic foot muscles. We compared TcMEP responses between these muscle groups using paired t-test statistical analysis. Each limb was analyzed separately. Only limbs without deficit in the interested muscle groups were included for analysis. Results: A total of 40 patients and 69 limbs were included for analysis. The mean TcMEP amplitude difference between the tibialis anterior and quadriceps muscles was 458 µV ( P < 0.0001), and between intrinsic feet and quadriceps muscles was 541 µV ( P < 0.0001). Proximal muscles also demonstrated a significantly smaller number of TcMEP phases than their distal counterparts. Conclusions: Transcranial motor evoked potential amplitudes are significantly smaller in proximal lower extremity muscles compared with distal lower extremity muscles. The observed difference might be due to cortical representation or higher subcutaneous tissue in thigh muscles.